A new harvestman species of the genus Nelima (Opiliones: Sclerosomatidae) from Extremadura, Spain - Wijnhoven, Hay (Zootaxa, 2024)
A new Nelima species from Extremadura, Spain, is described as Nelima monfraguense sp. nov. The male is characterised by its dark dorsal colour, robust pedipalps armed with denticles, short, robust legs with extremely short and enlarged femora I and III, and by its penial morphology; both sexes have trichomes on all leg femora and patellae. The species was found in an open woodland area, a ‘dehesa’ landscape near the Monfragüe National Park. A discussion on related Iberian species of the genus is included.